Some integral equations for the Szego and the Bergman kernels. - Murid, Ali H.M. (Jabatan Matematik Universiti Teknologi Malaysia, 1995)
The Szego and the Bergman kernel functions are known to satisfy a certain integral equation of the second kind. A generalized integral equation is formulated such that both the integral equation for the Szego and the Bergman kernels can be derived. This general formulation also yields singular integral equations of the first and the third kinds for the Szego and the Bergman kernels.